Crystal structure of 6-chloro-5-isopropylpyrimidine- 2,4(1H,3H)-dione - Haress, Nadia G.; Ghabbour, Hazem A.; El-Emam, Ali A.; C. S., Chidan Kumar; Fun, Hoong Kun (International Union of Crystallography, 2014)
In the molecule of the title compound, C7H9ClN2O2, the conformation is determined by intramolecular C—H O and C—H Cl hydrogen bonds, which generate S(6) and S(5) ring motifs. The isopropyl group is almost perpendicular to the pyrimidine ring with torsion angles of 70.8 (3) and 56.0 (3). In the crystal, two inversion-related molecules are linked via a pair of N—H O hydrogen bonds into R2 2(8) dimers; these dimers are connected into chains extending along the bc plane via an additional N—H O hydrogen bond and weaker C— H O hydrogen bonds. The crystal structure is further stabilized by a weak – interaction [3.6465 (10) A ° ] between adjacent pyrimidine-dione rings arranged in a head-to-tail fashion, producing a three-dimensional network.